THE INFLUENCE OF LEARNING MOTIVATION AND GRIT ON THE GROWTH MINDSET OF SENIOR HIGH SCHOOL STUDENTS IN THE ANAMBAS ISLANDS - Sasa Raci; Risydah Fadilah; Salamiah Sari Dewi (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
The purpose of this study was to determine the influence of Learning Motivation and Grit on Growth Mindset among senior high school students in the Anambas Islands. This research employed a quantitative method with a total population of 324 students and a sample of 235 respondents. The sampling technique used was probability sampling, and the data analysis technique applied was multiple regression analysis. Based on the results of hypothesis testing, the multiple regression analysis showed that the regression coefficient of the Learning Motivation variable (t-calculated) was 2.458, with a t-table value of 1.651. The significance value of Learning Motivation toward the related variable, Growth Mindset, was 0.000 < 0.05. Furthermore, the regression coefficient of the Grit variable (t-calculated) was 2.803, with a t-table value of 1.651, and the significance value of Grit toward Growth Mindset was 0.001 < 0.05. Additionally, based on the F-test results, the F-calculated value was 46.675, while the F-table value was 3.041, with a significance value of 0.000 < 0.050. Thus, since F-calculated > F-table and the significance value is below 0.050, it can be concluded that Learning Motivation and Grit simultaneously have a significant influence on students’ Growth Mindset.